Análisis de la Morosidad del Crédito Microempresarial de la Cooperativa de Ahorro y Crédito Codesarrollo Ltda.-Agencia Loja en los periodos 2011-2012. - Castillo Zhingre, Ruth de los Ángeles (2016)
The loan portfolio represents one of the largest sources of revenue for a financial institution , the same is accompanied by various lines of credit such as consumer, commercial , housing, microenterprise , etc. , is also a major causal risk if no precautionary measures are taken to any negative aspect , which is why it has seen fit to make this thesis titled "Analysis of microenterprise credit arrears of Savings and Credit Cooperative Ltd. CODESARROLLO Agency -Loja in the period 2011-2012 " the same that aims to publicize whether the administration of the portfolio has performed adequately , for which tools for the financial analysis , ratios and financial indicators and the level of risk is applied with their respective rating , so that managers have a useful tool that allows them to make appropriate decisions. It is noteworthy that the Savings and Credit Cooperative " Co-development " Loja Agency Ltd. , has 96% in the total loan portfolio of assets, in which microenterprise credit represents 55 % in its loan portfolio. Sustained theoretical content to this report were used , plus the use of scientific , deductive , inductive, analytical and statistical methods that allowed the collection of information for the development of research , then a general diagnostic information obtained was performed by the institution as: background , legal basis , mission, vision , etc. allowing to know the administrative activities of the institution . Once the general objective is to analyze the microenterprise credit delinquencies Agency Codesarrollo 2011-2012 periods in the city of Loja, he posed for compliance necessary, raising five specific objectives : to analyze the microcredit portfolio in terms amounts, terms and numbers appropriations, allowing to know that most microfinance loans are in amounts of $ 200 to $ 5000 with a current portfolio of over delinquent , have set 1397 credits in 2011 and 563 in 2012 , where period of time to cancel is mostly for 4 years. The second objective was to apply vertical and horizontal analysis, vertical analysis which allowed us to evaluate the capacity of cooperative loans, establishing the participation of the accounts of the total loan portfolio, the horizontal analysis determined the increases and decreases in accounts the total loan portfolio in 2011 and 2012 periods. Apply financial indicators related to microenterprise credit portfolio , reflecting that the entity has good solvency of 108.60 %, resources needed to meet their obligations, the productive asset in 99.69 %, with assets of 8.97 unproductive liquid % which means that the institution is investing in funds available. A percentage of delinquent portfolio of 4.87% was found at the boundary of its parameter set. The rating of the customers based on their payment behavior , classifies them into categories defined according to the rules , which is why in the Cooperative microcredit normal risk corresponding to the category A- 3 were found ; potential risk loans in Category B2 , with poor risk category C2 credit risk and doubtful in Category D and risk of loss category E. To determine the factors that affect the delinquency of microcredit and establish alternative collections that can be adopted in Codesarrollo Agency , for which six matrices that help optimize recovery management portfolio was done more efficiently and decrease in large proportion delinquency. . Finally the respective conclusions and recommendations to improve the financial institution arise.